STMO-01 APPLICATION OF THE AMINOLEVULINIC ACID HYDROCHLORIDE FOR INTRAOPERATIVE DETECTION OF MALIGNANT BRAIN TUMORS. (16th December 2019) - Kobayashi, Keiichi; Saito, Kuniaki; Shimada, Daisuke; Matsumoto, Yoshie; Shimizu, Saki; Iijima, Shouhei; Noguchi, Akio; Shibahara, Jyunji; Shiokawa, Yoshiaki; Nagane, Motoo
Abstract: BACKGROUND: A maximal safe resection has been shown as an independent prognosis factor for high grade glioma (HGG). Intraoperative photo dynamics diagnosis (PDD) facilitates an increased rate of tumor resection, thereby taking an important role in accomplishment of " maximal safe resection " along with neuro-navigation and monitoring of motor nerve function. Since the approval of aminolevulinic acid (5-ALA) for PDD in 2013 in Japan, we have been utilizing the PDD when HGG is suspected by preoperative assessments. Here we retrospectively analyze clinical findings in PDD-mediated tumor resection. METHODS: From February 2014 to March 2019, 285 consecutive patients (132 females) with suspected HGG underwent total of 302 PDD-mediated resection. Median age was 61 yo (13–90). A single oral dose of 5-ALA 20 mg/kg was given within three hours before microsurgery. Positivity of excited fluorescence was assessed qualitatively under surgical microscope. RESULTS: Among 195 gliomas, the fluorescence positivity rates were 89.6% (120/134) for glioblastoma, 40.5% (15/37) for grade III, and 13.6% (3/22) for grade II. The positive rates for other histologies were 30.2% (13/43) for malignant lymphoma, 32.1% (9/28) for metastatic brain tumor, 0% (0/7) for meningioma (include atypical), and 4.5% (1/22) for other types. In gliomas the high positivity correlated with histological grades, while all fluorescence-positive grade II gliomas were recurrent tumors. Serious adverse events were not observed. CONCLUSIONS: The qualitative PDD showed a clinical utility to aid accurate resection in glioblastoma, whereas its positivity was inconsistent in lower grade gliomas as well as other malignant brain tumors. This unreliability might attribute, at least in part, to fluorescent intensity heterogeneity in situ, a reduced excitation by an inappropriate radiation angle of the light source, and the qualitative fluorescence detection. Impacts of introducing quantitative detection system as well as molecular and histopathological features on better discrimination will be discussed.